PENDAMPINGAN IMPLEMENTASI SISTEM INFORMASI BERSAMA ANTAR SEKOLAH (SIBAS) UNTUK MENDUKUNG TRANSFORMASI DIGITAL DI SMA NEGERI 1 PADANG PANJANG - Januardi Nasir; Yasha Langitta Setiawan (ASOSIASI IDEBAHASA KEPRI, 2026)
The use of information technology in school management is a crucial requirement to support the effectiveness of administration and academic services. SMA Negeri 1 Padang Panjang has been using information technology and the national data collection system DAPODIK, but the school's internal data management is still not optimally integrated across work units. This condition causes data disintegration that has the potential to hinder the efficiency of school information management. This community service activity aims to implement, socialize, and educate the school about the use of the SIBAS (Joint Information System Between Schools) system as an integrated school information system. The implementation method includes needs analysis, system installation and configuration, socialization, and mentoring the school in using SIBAS. The results of the activity indicate an increase in the school's understanding of the importance of an integrated information system and the ability to utilize SIBAS to support the management of academic data, administration, and school information services. Thus, the implementation of the SIBAS system at SMA Negeri 1 Padang Panjang is expected to support the realization of more effective, efficient, and information technology-based school management.